Family businesses successors knowledge and willingness on sustainable innovation: The moderating role of leader's approval - Yun-Zhong Wang; Fang Yi Lo; Shan-Ming Weng (Journal of Innovation & Knowledge (JIK), 2019)
Small and medium-sized enterprises (SMEs) in Taiwan have made undeniable contributions to the rapid economic development of Taiwan over the last decades. In Taiwan's economic system, over 90% of businesses are SMEs. However, with the increasingly severe problems of population aging, labor demands, and talent development falling far below expectations, all small and medium-sized family businesses in Taiwan will face succession difficulties in the coming decade. In view of this, this study was mainly to discuss the issue of business succession, focus on the status of business successors, and analyze the impact of successor knowledge and succession willingness on corporate sustainable innovation and successful business succession. Moreover, this study also noted that leader approval would affect the relationship between business successor and sustainable innovation. In other words, the leadership positions of family businesses in Taiwan are generally held by elders, and they are often not willing to delegate their powers, thus, leader's willingness to delegate their power to and approval of the successor would be crucial to the successor's willingness to succeed in the family business.
Keywords: 650; Business succession; Family business; Leader approval; Sustainable innovation